Standardisasi Layanan Penerjemahan di Indonesia: Sebuah Pemikiran Awal - Sukma, Bayu Permana; Khatimah , Husnul (Jurnal Penerjemahan, 2019)
The development of the foreign-oriented manufacturing industrial sector in Indonesia brings consequences to the increase of the need for translation services. It eventually has consequences to the need of standardization of translators and standardization of translation services which have not been available. This study aims to discuss the standardization of interpreting and translation services abroad which can be used as a reference for standardizing translation services in Indonesia, as well as how Indonesia significantly requires standardization of interpreters and translators. This study adopts a qualitative-descriptive approach. The data collection technique is study of document using content analysis. The results of the study show that foreign countries, particularly developed ones such as the United States and some European Union countries have standardized their translation services in order to improve the quality of translation and the quality of services of translation-service providers. In addition, standardization of translation in Indonesia is necessarily needed in order to give benefits for translation service providers to be able to provide good quality translation and standardized services. In other words, standardization is highly required to provide a benchmark and guidance regarding the translation services and products. Keywords: standardization, translation services, interpreter and translator.